2018
DOI: 10.1007/s10926-018-9793-7
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Quality of Life Among Massage Therapists with Visual Impairment

Abstract: Purpose The aim of this study was to evaluate the level of burnout syndrome and quality of life (QoL) among Polish massage therapists, and determine their relationship with sociodemographic and work-related variables. Methods A group of 43 participants aged 28-63, who were blind or poor-sighted were recruited for the study. They were surveyed with sociodemographic data questionnaire and the Polish versions of the Maslach Burnout Inventory-General Survey and WHOQOL-BREF. Results The overall level of exhaustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…This finding is not surprising as the health care environment is increasingly strained for nurses, and nursing shortages have become a serious global problem (Liu, Zhang, et al, 2012). In addition, our study demonstrated a significant negative correlation between nurses' job TA B L E 1 Univariate analysis of quality of working life with different demographic and work-related characteristics (n = 2,504) (Naz, Hashmi, & Asif, 2016;Wrzesińska et al, 2019), and our research differed from these studies because it examined the correlation between job burnout and QoWL, which was mainly influenced by one's full-time profession, rather than overall QoL. Moreover, multiple linear regression analysis indicated that job burnout was the most important factor affecting nurses' QoWL.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…This finding is not surprising as the health care environment is increasingly strained for nurses, and nursing shortages have become a serious global problem (Liu, Zhang, et al, 2012). In addition, our study demonstrated a significant negative correlation between nurses' job TA B L E 1 Univariate analysis of quality of working life with different demographic and work-related characteristics (n = 2,504) (Naz, Hashmi, & Asif, 2016;Wrzesińska et al, 2019), and our research differed from these studies because it examined the correlation between job burnout and QoWL, which was mainly influenced by one's full-time profession, rather than overall QoL. Moreover, multiple linear regression analysis indicated that job burnout was the most important factor affecting nurses' QoWL.…”
Section: Discussionmentioning
confidence: 56%
“…However, evidence of negative correlation between burnout and QoWL remains limited. Many previous studies have already reported the relationship between burnout and poor quality of life (QoL) in different occupations (Naz, Hashmi, & Asif, ; Wrzesińska et al, ), and our research differed from these studies because it examined the correlation between job burnout and QoWL, which was mainly influenced by one's full‐time profession, rather than overall QoL. Moreover, multiple linear regression analysis indicated that job burnout was the most important factor affecting nurses' QoWL.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…11,21,40,41,47,48 As with most jobs, but particularly with contingent work that involves working with multiple clients during a shift (ie, gigs), time availability is a recurring issue raised by employees. [49][50][51] Time was a critical factor related to implementing self-care practices across all MTs, both as a facilitator and barrier. Based on the regression models, when time was a facilitator, it was associated with implementing an average of 2.1 more self-care practices; in contrast, when time was identified as a barrier it was associated with implementing 0.9 fewer self-care items despite wanting to make these changes.…”
Section: Discussionmentioning
confidence: 99%
“…As with most jobs, but particularly with contingent work that involves working with multiple clients during a shift (ie, gigs), time availability is a recurring issue raised by employees 49–51 . Time was a critical factor related to implementing self-care practices across all MTs, both as a facilitator and barrier.…”
Section: Discussionmentioning
confidence: 99%